Кариотипы Microtus obscurus на территории Азербайджанской Республики - Азизов, И.В.; Кулиев, Г.Н.; Мамедрзаева, Э.Т.; Шамилов, Э.Н.; Абдуллаев, А.С.; Шамилли, В.Э.; Кулиев, А.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Karyotypes of common vole (Microtus obscurus) distributed in mutations have been registered. Methods. The structure of this chromosome was analyzed by G and C-banding methods. In the fifth pair of chromosomes in some specimens of common vole caught in the Azerbaijan territory (Kedabek district). Due to the fact that in one of the chromosome at which the mutation was detected occurs pericentric invertsiya, it is converted into the acrocentric form. Conclusions.A hybridization between different of heterochromatine and constituent parts of the nucleolus two populations of common voles Big (population of Pirguli) and Lesser Caucasus (population of Kedabek) was carried out. Results. The resulting hybrids were sterile.

Key words: heterochromatine, chromosome, C-banding, population.